Metallogenesis, hydrocarbons and tectonic patterns in Eastern Asia a program of research. (Committee For Co-ordination of Joint Prospecting for Mineral Resources in Asian Offshore Areas (CCOP) and Intergovernmental Oceanographic Commision (IOC), UNESCO, 1973)
At head of title: International Decade of Ocean Exploration.Bibliography: p. 151-158